DAMPAK REGENERASI PETANI PADA KETAHANAN PANGAN LOKAL KUBU RAYA KALIMANTAN BARAT - Putri, Nidya Ramdhani; Prasetyo, Riko; Wulansari, Fidia (Institute of Computer Science (IOCS), 2024)
Farmers have an important role in the sovereignty of a nation, because it is the farming profession that plays a role in maintaining food stability nation. Indonesia is an agricultural country, with the majority of its population working in agriculture, depends on the success of the farmer to supporting food security in Indonesia. Farmers in Indonesia assist the government in meeting food needs. Therefore, farmers existing in Indonesia must be carefully considered so that Indonesia can continue to supply food sourced from domestic farmers. But Reduced food production data can also be caused by factors. Another thing that is important to be addressed immediately is the problem of farmer regeneration. The aim of this research is to find out what food crisis is occurring. This is really caused by the regeneration of farmers, especially in Kubu Raya Regency. The research method is a survey method by analyzing data using the Cobb-Douglas formula using SPSS 21 software.